A design methodology for affective Virtual Reality. Issue 162 (June 2022) - Dozio, Nicoló; Marcolin, Federica; Scurati, Giulia Wally; Ulrich, Luca; Nonis, Francesca; Vezzetti, Enrico; Marsocci, Gabriele; La Rosa, Alba; Ferrise, Francesco
Highlights: We designed ten virtual environments able to elicit a specific emotional reaction. We describe the methodology we used to design the emotional virtual environments. The methodology is based on the use of semantic elements and valence, arousal and dominance. The results show that the designed virtual environments elicit the desired emotions and arousal-valence-dominance levels. Abstract: In the era of 'metaverse', virtual environments are gaining popularity among new multimedia contents and are also recognized as a valuable means to deliver emotional content. This is favoured by cost reduction, availability and acceptance by end-users of virtual reality technology. Creating effective virtual environments can be achieved by exploiting several opportunities: creating artificial worlds able to generate different stories, mixing sensory cues, and making the whole interactive. The design space for creating emotional virtual environments is ample, and no clear idea of how to integrate the various components exists. This paper discusses how to combine multiple design elements to elicit five distinct emotions. We developed and tested two scenarios per emotion. We present the methodology, the development of the case studies, and the results of the testing.